Research on the knowledge security - Shi-jie YAN; Le-quan MIN; Xiu-bin FAN (Tongxin xuebao)
Based on previous researches,the formal definitions of data,huge data,information and knowledge is given,seven attribute for knowledge security are proposed:confidentiality,integrity,availability,controllability,verifiability,inheritability,and anti-whiteness and related prevention technology,the relation between huge data and the center limit theorem is discussed,the concept of secure knowledge system is introduced.